2017
DOI: 10.1371/journal.pone.0184286
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tagging of rehabilitated green sea turtles Chelonia mydas from the United Arab Emirates, including the longest tracked journey for the species

Abstract: We collected movement data for eight rehabilitated and satellite-tagged green sea turtles Chelonia mydas released off the United Arab Emirates between 2005 and 2013. Rehabilitation periods ranged from 96 to 1353 days (mean = 437 ± 399 days). Seven of the eight tagged turtles survived after release; one turtle was killed by what is thought to be a post-release spear gun wound. The majority of turtles (63%) used shallow-water core habitats and established home ranges between Dubai and Abu Dhabi, the same area in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…This is in general accordance with previous studies with rehabilitated individuals that have shown no major anomalies in post-release behaviour (e.g. Polovina et al 2006;Rees et al 2013;Robinson et al 2017; but see also Cardona et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…This is in general accordance with previous studies with rehabilitated individuals that have shown no major anomalies in post-release behaviour (e.g. Polovina et al 2006;Rees et al 2013;Robinson et al 2017; but see also Cardona et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…These assessments are necessary for establishing protected areas and maintaining habitat quality to ensure recovery of threatened and endangered species. While numerous studies have examined the migratory movements of adult female sea turtles between nesting beaches and foraging grounds (Seminoff et al, 2002(Seminoff et al, , 2008MacDonald et al, 2012MacDonald et al, , 2013Bradshaw et al, 2017;Robinson et al, 2017;Dutton et al, 2019), fewer studies have focused on the habitat use patterns of juvenile, neritic stage turtles (Godley et al, 2008;Coleman et al, 2017). Understanding the habitat needs of juvenile-stage sea turtles is a necessary component of managing population recovery because survival and maturation of this stage will eventually impact future reproduction and population growth (Crowder et al, 1994;Heppell et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods, such as aerial survey [ 10 14 ], snorkeling survey [ 14 , 15 ] and telemetry [ 16 ] (e.g., very high frequency telemetry, sonic telemetry and satellite telemetry), have been used to study and monitor the population and distribution of sea turtles. Data acquisition systems such as GPS tracking, geolocating tags, time-temperature-depth recorders, and heart rate counters were also been used to monitor their behavior and physiology [ 16 – 20 ]. Another method suggestively having great potential for studying turtle behavior is to study the epibiota on shell turtles.…”
Section: Introductionmentioning
confidence: 99%